Electron microscopic morphometry of podocyte foot process effacement as a tool to distinguish primary from secondary focal segmental glomerulosclerosis (FSGS) - da Costa, Nelson (Department of Clinical Laboratory Sciences, 2025)
Background: Focal segmental glomerulosclerosis (FSGS) is a histological pattern of glomerular injury and one of the most common causes of end-stage renal disease in adult patients. Two major subtypes of FSGS (primary oand secondary) have been identified, with differences in clinical presentation, electron microscopy (EM) foot process width (FPW) and effacement (FPE), and treatment options. Primary FSGS commonly presents as nephrotic syndrome (NS), shows diffuse FPE with a FPW >1500nm, and is generally responsive to steroid therapy. Secondary FSGS does not present with NS (non-nephrotic), shows focal FPE and a FPW <1500nm, and does not respond to steroids. Sometimes, it may be clinically very difficult to differentiate between the two. In these scenarios, EM becomes of paramount importance. In this study, we evaluated podocyte FPW and FPE in FSGS patients to investigate whether a significant difference exists between primary and secondary FSGS. Methods: Cases histologically diagnosed as FSGS in adult native renal biopsies over a 5-year period at Groote Schuur Hospital and Livingstone Hospital were reviewed. Using the 2021 KDIGO guidelines, cases were classified as nephrotic syndrome (NS) or non-nephrotic syndrome (NNS). Using EM and imaging software, podocyte FPWs were calculated and the extent of FPE determined for each case. The results were analysed and correlated with multiple variables. Results: Of a total sample size of 35, 32 cases of FSGS and 3 controls were reviewed. 23 patients presented with NS while 9 patients did not meet the criteria for NS. The NS group had a calculated median FPW of 3076nm, while the NNS group had a median FPW of 1322nm (p=0.003). 83% of the NS group had diffuse FPE, whereas 78% of the NNS group had focal FPE (p=0.003). Logistic regression revealed a FPW threshold value of 2550nm correlated with an 80% probability of a NS diagnosis. A strong correlation between primary FSGS and oedema (p=0.006), proteinuria (p=0.0005), cholesterol (p=0.003) and albumin (p=0.0002) were found. A strong correlation existed between FPW and proteinuria (p=0.0021), eGFR (p=0.017), and albumin (p=0.012). No differences were identified with regards to age, gender, and HIV status. Unsupervised hierarchical cluster analysis with no a priori assumptions identified three clusters, one NNS cluster and two NS clusters, the latter demonstrating 2 separate populations differing with respect to uPCR, creatinine, and FPW. The significance of this finding will be investigated in follow up studies. Conclusion: This is the first study, to our knowledge, in the sub-Saharan African setting to use EM to calculate FPW and determine FPE in FSGS patients. The current study results align with those of previously published international studies. In this study, primary FSGS is generally associated with diffuse FPE and FPW>3000nm, whereas secondary FSGS is associated with focal FPE and FPW <1500nm. In clinically difficult scenarios, EM FPW calculation and FPE determination remains an important adjunct to histopathology and clinical parameters in the differentiation of primary from secondary FSGS in the South African population. The significance of making this distinction lies in completely different patient management regimens between the two groups.